The Correlation between Body Image and Physical Activity in Female Students of State Senior High School 2 Surabaya (SMA Negeri 2 Surabaya) - Nandia Firsty Dhorta; Lailatul Muniroh (Amerta Nutrition, 2021)
ABSTRACTBackground: Nutritional problems, such as over-nutrition and under-nutrition, will raise the risk of non-communicable diseases. Adolescence happens to be one of the most important phase in life since it is a transition phase to adulthood so that nutritional status at this phase could define the health status in adulthood. The limitation of outdoor activities during the pandemic has been done as an effort to break the chain of the Covid-19 virus spread causes decline in physical activity, increase in sedentary behavior and stressful events in the form of a negative body image. Changes in physical activity and the presence of a negative body image, especially in adolescent girls, will likely cause changes in nutritional status and increase the risk of nutritional problems in both over-nutrition and under-nutrition.Objective: To analyze the relationship of body image and physical activity of female students in State Senior High School 2 Surabaya (SMA Negeri 2 Surabaya).Methods: The study design was a cross-sectional study, with a total sample of 61 female students of SMA Negeri 2 Surabaya, aged 15-17 years who were randomly selected using the simple random sampling method. The study instruments were BSQ-16a, IPAQ-short form, personal data including body height and body weight which were designed online. Data analysis were cross tab analysis and the fisher’s exact test using IBM SPSS Statistics v23.Results: There were seven out of ten (70.5%) students that had a negative body image; most of them had normal nutritional status (77%), but the prevalence of overweight (14.8%) was high and the levels of physical activity varied (light=32.8, moderate=31.1%, strenuous=36.1% ). In addition, there was a correlation between body image (p = 0.011) and physical activity (p = 0.006) with nutritional status of female students in SMA Negeri 2 Surabaya.Conclusion: Negative body image and lower physical activity or sedentary behavior contributed to overweight and obesity in female students of State Senior High School 2 Surabaya (SMA negeri 2 Surabaya).